Life on the frontier: Roman military families in Lower Moesia - Tomas, Agnieszka (Studia Europaea Gnesnensia, 2017)
The epigraphic evidence from four Lower Moesian legionary bases provides information about military-civilian society living along the Lower Danubian frontier zone. The inscriptions on stone originating from these four sites informs not only about the names, age or status of the people living in the border zone, but may be helpful in recreating the emergence of Roman provincial society in the military garrisons. The epigraphic evidence collected from Oescus, Novae, Durostorum, and Troesmis includes only the inscriptions related to the people who were not active soldiers and officers serving in the legions. The aim of the paper is to find out whether the epigraphic evidence may bring any additional information concerning the civilian and military families, ethnic and social composition of the inhabitants living near legionary bases, conditions of life, and the nature of the settlement.